Technological Knowledge And Market Orientation In New Products Performance: The Role Of Absorptive Capacity - Suyono Saputra; Stella Stella; Wisnu Yuwono (UNIVED Press, 2025)
Due to increasing competition in the global market, companies from all industries worldwide are facing constantly changing conditions. Changes drive companies to rebuild their trade models and enhance their products and services in order to maintain competitiveness and ensure survival. The ease of replication by competitors or elsewhere underscores the importance of adapting to change. The analyst distributed self-administered surveys via email to specific sources involved in the development of unused items since October 2023. The methodological design is crucial for this quantitative research, which focuses on a population of manufacturing companies in Batam, Tanggerang, Tangjung Pinang, and other districts. The factual strategies chosen to analyze the theories proposed in this study involve using the Smart PLS and SPSS applications. The findings suggest that: 1) Market Orientation does not affect on New Product Performance. 2) Market Orientation positively influences Absorptive capacity. 3) Technological Knowledge competence positively impacts New Product Performance. 4) Absorptive Capacity has a positive and significant effect on New Product Performance. 5) Technological Knowledge positively affects Absorptive Capability as an intervening variable. Having a positive organizational mindset increases the correlation between Advertising Introduction and New Product performance. When companies have limited ability to benefit from unpredictable market factors and wish to benefit from Market Introduction in New Product Performance activities, they must recognize the unpredictable nature of the current market.